2016
DOI: 10.1152/ajprenal.00551.2015
|View full text |Cite
|
Sign up to set email alerts
|

A mild reduction of food intake slows disease progression in an orthologous mouse model of polycystic kidney disease

Abstract: Kipp KR, Rezaei M, Lin L, Dewey EC, Weimbs T. A mild reduction of food intake slows disease progression in an orthologous mouse model of polycystic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 26 publications
3
77
2
1
Order By: Relevance
“…Because water intake remained higher in the TD treatment group compared to the other groups and responded to titration steps, a lower food intake and consequently, possibly a lower dose of the V2RA is not a concern. Nevertheless, recent studies in mice revealed that a lower food intake can also be protective in ADPKD [29,30]. Although food intake (adjusted for body weight) in the TD treatment group was similar after 6 weeks of study in comparison to the FD treatment group, body weight was markedly different between these study groups at the end of our experiment.…”
Section: Discussioncontrasting
confidence: 58%
“…Because water intake remained higher in the TD treatment group compared to the other groups and responded to titration steps, a lower food intake and consequently, possibly a lower dose of the V2RA is not a concern. Nevertheless, recent studies in mice revealed that a lower food intake can also be protective in ADPKD [29,30]. Although food intake (adjusted for body weight) in the TD treatment group was similar after 6 weeks of study in comparison to the FD treatment group, body weight was markedly different between these study groups at the end of our experiment.…”
Section: Discussioncontrasting
confidence: 58%
“…Consistent with this hypothesis, mild-to-moderate food restriction was recently shown to slow progression in multiple mouse models of ADPKD, concomitant with suppressed mTOR signaling and AMPK activation. 12,13 Obesity is a well established independent risk factor for incident CKD, 6,34,35 ESRD,7,8 and decline in eGFR in the general population. 36 In individuals with prevalent CKD, obesity is associated with a decline in eGFR in some 8,37 but not in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…have suggested that ADPKD is a state of defective glucose metabolism and metabolic reprogramming. 10,11 Furthermore, mild-tomoderate food restriction slows disease progression in multiple mouse models of ADPKD, 12,13 suggesting that changes in energy status may have a profound effect on ADPKD progression.…”
mentioning
confidence: 99%
“…and metabolic reprogramming are effective approaches for slowing cyst expansion and disease progression in murine models of ADPKD (7,18). In particular, we and others have demonstrated the protective effects of mild to moderate calorie/food restriction (FR) (10%-40% decrease in total caloric intake) in multiple murine models of ADPKD (18,19). In addition to that, a recent study reported that time-restricted feeding and ketosis led to protective effects against ADPKD in rat, mouse, and feline models of ADPKD (20).…”
Section: Introductionmentioning
confidence: 99%
“…FR without malnutrition extends lifespan and increases resistance to age-related diseases in rodents and monkeys, improves the health of overweight humans, and has recently been reported to delay the progression of ADPKD (8,9,18,19,21,22). Interestingly, the beneficial effects of FR in aging and life span appear to be mediated in large part by suppression of the IGF pathway (8,9,21,22).…”
Section: Introductionmentioning
confidence: 99%